Unlocking JAKi Potential: Redefining Axial Spondyloarthritis Treatment Paradigms - Andrew Östör (Journal of Clinical Rheumatology and Immunology)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that primarily affects the axial skeleton, encompassing both radiographic and non-radiographic forms. The disease is characterized by chronic back pain and spinal stiffness, which are the most common symptoms. However, it often includes peripheral manifestations and extra-musculoskeletal symptoms as well, making the clinical presentation quite diverse. JAK inhibitors work by blocking the intracellular signaling pathways of several proinflammatory cytokines, which play a crucial role in the pathogenesis of inflammatory diseases. Given their proven efficacy in managing rheumatoid arthritis and their ability to mediate the signaling of cytokines involved in the pathogenesis of axSpA, JAK inhibitors have been the subject of numerous clinical trials in this context. The Assessment of SpondyloArthritis international Society and the European Alliance of Associations for Rheumatology (ASAS-EULAR) joint recommendations provide comprehensive guidance for the management of axSpA in 2022. The guideline introduced the use of Janus kinase inhibitors (JAKi), as a completely new drug class in the treatment landscape, with efficacy demonstrated in radiographic axSpA. JAKi was recommended, as a means to treatment intensification, in axSpA patients with persistently high disease activity despite conventional treatment. Since then, more trial data results have been released, showing efficacy in non-radiographic axSpA population as well. In this lecture, Professor Östör will delve into the critical role of shared decision-making in the management of axial spondyloarthritis. He will emphasize the importance of tailoring treatment plans to individual patient preferences and clinical profiles, a practice that is increasingly recognized as vital in achieving optimal outcomes. By examining current international guidelines and the latest study data, Professor Östör will provide a comprehensive overview of the benefit-risk profile of Upadacitinib in the treatment of axSpA. Professor Östör will also share his clinical experience with Upadacitinib, discussing various case studies to illustrate its application in real-world settings. This will include an exploration of how patient preferences and clinical profiles can influence treatment decisions, ensuring a personalized approach to managing this complex disease.